2019
DOI: 10.1039/c9fo01233h
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of the cell membrane and inhibition of cell phosphatidic acid biosynthesis inStaphylococcus aureus: an explanation for the antibacterial mechanism of morusin

Abstract: Morusin from mulberry inhibits the growth of S. aureus by destroying its cell membrane and further moderating the phosphatidic acid biosynthesis pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…It is worth mentioning that our previous investigations on morusin and kuwanon G found irrelevant antibacterial effects against Gram-negative bacteria ( E. coli , P. aeruginosa ) (data not shown). With respect to morusin, our results are in agreement with previous studies reporting very good and good antibacterial effects against MSSA and S. epidermidis (MIC = 6.30 – 25 and 20 µg/mL, respectively) but moderate and low activity against Gram-negative bacteria (MIC = 62.5 µg/mL against P. aeruginosa, MIC > 100 µg/mL against E. coli ) ( Mazimba et al, 2011 , Pang et al, 2019 , Sohn et al, 2004 , Wu et al, 2019 , Zuo et al, 2018 ). Zuo et al (2018) have recently reported very good to moderate antibacterial effects for morusin against clinical MRSA isolates (MIC = 8 – 32 µg/mL).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It is worth mentioning that our previous investigations on morusin and kuwanon G found irrelevant antibacterial effects against Gram-negative bacteria ( E. coli , P. aeruginosa ) (data not shown). With respect to morusin, our results are in agreement with previous studies reporting very good and good antibacterial effects against MSSA and S. epidermidis (MIC = 6.30 – 25 and 20 µg/mL, respectively) but moderate and low activity against Gram-negative bacteria (MIC = 62.5 µg/mL against P. aeruginosa, MIC > 100 µg/mL against E. coli ) ( Mazimba et al, 2011 , Pang et al, 2019 , Sohn et al, 2004 , Wu et al, 2019 , Zuo et al, 2018 ). Zuo et al (2018) have recently reported very good to moderate antibacterial effects for morusin against clinical MRSA isolates (MIC = 8 – 32 µg/mL).…”
Section: Resultssupporting
confidence: 92%
“…In an attempt to elucidate the mechanisms underlying their antibacterial potential, morusin and kuwanon G have been recently investigated with respect to their effects on MSSA membrane; both compounds were found to disrupt the bacterial membrane ( Pang et al, 2019 , Wu et al, 2019 ). In the present study, we examined their effects on the integrity and morphology of MRSA ( S. aureus ATCC 43300) membrane using the fluorescence and differential interference contrast microscopy and SEM, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morusin is an isoprenylated flavone purified from the root bark of Morus alba Linn, exerting numerous health benefits including antinociceptive, antidiabetic, anticonvulsant, antibacterial, and antitumor activities [52][53][54]. In particular, the high antitumor capacity has been intensively tested across many different cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Quercitrin, morusin, salicin, and cinnamaldehyde possess known biological activities [26][27][28][29]. The latter three substances are transferred from their respective host trees and accumulate within TH.…”
Section: Discussionmentioning
confidence: 99%